A Pilot Study of Iyengar Yoga for Pediatric Obesity: Effects on Gait and Emotional Functioning - Hainsworth, Keri R. (Children (Basel), 2018)
Obesity negatively impacts the kinematics and kinetics of the lower extremities in children and adolescents. Although yoga has the potential to provide several distinct benefits for children with obesity, this is the first study to examine the benefits of yoga for gait (primary outcome) in youths with obesity. Secondary outcomes included health-related quality of life (HRQoL), physical activity, and pain. Feasibility and acceptability were also assessed. Nine youths (11–17 years) participated in an eight-week Iyengar yoga intervention (bi-weekly 1-h classes). Gait, HRQOL (self and parent-proxy reports), and physical activity were assessed at baseline and post-yoga. Pain was self-reported at the beginning of each class. Significant improvements were found in multiple gait parameters, including hip, knee, and ankle motion and moments. Self-reported and parent-proxy reports of emotional functioning significantly improved. Time spent in physical activity and weight did not change. This study demonstrates that a relatively brief, non-invasive Iyengar yoga intervention can result in improved malalignment of the lower extremities during ambulation, as well as in clinically meaningful improvements in emotional functioning. This study extends current evidence that supports a role for yoga in pediatric obesity.